A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

A modified-live PRRSV vaccine administered at weaning confers partial protection against a highly virulent PRRSV-1 strain throughout the grower-finisher period - A. Pey; P. Curto; E. Gurri; E. Aulinas; G. Ramirez; J. Molín; L. Fraile; A.M.M. Stoian (Research in Veterinary Science, 2026)

αB-crystallin elastin-like polypeptides for sustained ocular drug delivery - Sara Aly Attia; Amanda M. Tse; Ashley D. Ramirez; Maryam Izadiar; Ying Liu; Hao Guo; Angela Albanese; Whitaker Cohn; Adrienne W. MacKay; Paul M. Seidler; Ram Kannan; Parameswaran G. Sreekumar; et al. (Drug Delivery and Translational Research, 2026)

Comparison between different sun drying methods for dried vine production in relation to Aspergillus section Nigri presence and ochratoxin A accumulation - Yamila G. Kuhn; Susana G. Ferreyra; Eugenia Cendoya; Carolina Torres-Palazzolo; Eimi Riveira; Maria Laura Chiotta; Rodrigo Espindola; María Laura Ramirez; Mariana Combina; María Lorena Ponsone (International Journal of Food Microbiology, 2026)

Optimizing Photogrammetry Parameters for 3D Reconstruction of Fresh Brain Specimens - Carlos A. Rueda-Pérez; María-Camila Valencia-Loaiza; Paula Vega-Cordoba; Juliana Tobón; Dylan S. Anaya; Andres Gonzalez-Leyton; Juan F. Mazo; Jesús D. Tarazona; Santiago Ruiz; Juan G. Martinez; Andrés Echeverri-Garcia; Catherine J. Gomez-Moreno; et al. (Neuroinformatics, 2026)
Photogrammetry has become an essential tool in medical and research fields for generating high-fidelity 3D models from 2D images. However, optimizing the imaging and processing parameters remains a challenge, particularly for fresh brain specimens, where repeated imaging is not feasible. This study systematically evaluates the impact of various Metashape alignment settings on 3D reconstruction outcomes, analyzing 12,600 configuration combinations and 63,000 alignments. Our results suggest that the optimal imaging setup consists of four photo sets: two captured at anatomical position (level with the brain and 30 cm above it at a 30° camera tilt) and two identical sets with the basal side facing upwards. The brain should be rotated 3° between shots, generating 120 images per set. Initial processing should be performed without masks using medium-precision alignment in Metashape. If alignment fails, we recommend generating one mask per image, delineating the brain’s borders, and applying masks to key points. Notably, higher image density only improves alignment reliability when masking is selected to detected features and may only increase processing time. We also observed variability in alignment results under identical conditions, suggesting an inherent stochastic component in Metashape. Consequently, unsuccessful alignments should be repeated before modifying imaging parameters. To our knowledge, this is the first study to systematically define an optimal imaging and processing parameters for 3D photogrammetry of fresh brains using a turntable. Future research should focus on determining the minimum number of images required to ensure high-quality reconstructions.

A probabilistic framework for assessing seismic functionality loss and recovery in buildings using a spatially explicit functionality metric - Juan Gutiérrez; A. Gustavo Ayala; José G. Rangel-Ramirez; H. Rodrigo Amezcua; Carlos González‑Calva (Bulletin of Earthquake Engineering, 2026)

Injury Mechanics in Surfactant-Depleted and Healthy Rat Lungs: A Multi-scale Consideration of Artificial and Physiological Ventilation - M. Shankel; G. O. Ramirez; M. Eskandari (Annals of Biomedical Engineering, 2026)
Purpose Ventilator-induced lung injury (VILI) causes regional pulmonary damage and remains a medical challenge. While the clinical standard, positive-pressure ventilation (PPV), has been contrasted with physiological negative-pressure ventilation (NPV), the discrepancy between ventilation modes on VILI remains unstudied. Methods To elucidate possible VILI mechanics from alveolar overdistension and distortion, three groups of rat lungs were examined: uninjured controls, lungs subjected to high tidal volume with zero positive end-expiratory pressure to induce VILI, denoted VILI-Only, and surfactant-depleted VILI lungs. PPV and NPV mechanics were continuously assessed at the organ- and tissue-level with a custom-designed electromechanical apparatus paired to digital image correlation, where confocal microscopy confirmed microstructural damage. Results Compared to controls, VILI-Only increased regional strain by 6% while static compliance remained similar. Surfactant-depleted VILI lungs exhibited greater strain and compliance increases, and both injury groups showed elevated strain anisotropy. In VILI-Only lungs, NPV compared to PPV, reduced mean strain (9%), anisotropic distortion, and hysteresis (25%) relative to PPV, while promoting more isotropic deformation in right lung lobes. In surfactant-depleted VILI lungs, NPV reduced inflation compliance relative to PPV, but did not lessen regional strain. Notably, NPV revealed greater pressure relaxation in VILI-Only, a non-observed effect with PPV. Conclusion Altogether, VILI-Only and surfactant-depleted VILI produced elevated strain and anisotropic deformation, indicating damaging regional inflation. NPV revealed more prominent alterations in lung behavior, including pressure relaxation and strain significances, indicating improved sensitivity to early dysfunction. In VILI-Only lungs, NPV also reduced strain and anisotropy, suggesting physiological breathing may mitigate progressive VILI-induced mechanical damage.

Elevated levels of circulating plasma sPDGFRβ in cognitively impaired APOE4 carriers - Abhay P. Sagare; Trevor Lohman; Ivan Ramirez; Elizabeth B. Joe; Michael G. Harrington; Helena C. Chui; Lon S. Schneider; Hussein N. Yassine; John M. Ringman; Arthur W. Toga; Daniel A. Nation; Berislav V. Zlokovic (GeroScience, 2026)
Increased levels of cerebrospinal fluid (CSF) soluble platelet-derived growth factor receptor-β (sPDGFRβ), a marker of blood–brain barrier (BBB)-associated pericyte cell injury, have been shown to correlate with increased BBB permeability and severity of Alzheimer’s disease (AD) pathology. It has been also shown that increased CSF sPDGFRβ levels can predict cognitive dysfunction in APOE4 carriers bearing the main susceptibility gene for AD. Whether plasma sPDGFRβ levels are also elevated in APOE4 carriers has not been explored. Here, we analyzed plasma samples for sPDGFRβ levels, Ab 42/40 ratio, and pTau217 in 115 APOE3 homozygotes and APOE4 carriers with Clinical Dementia Rating (CDR) score of 0 and 0.5. Our data show that plasma sPDGFRβ levels are increased in APOE4 carriers with cognitive impairment compared to APOE4 carriers that are cognitively unimpaired as well as relative to cognitively impaired APOE3 carriers even after controlling for plasma Aβ 42/40 ratio and pTau217. Thus, our data suggest that plasma sPDGFRβ is a useful biomarker of brain pericytes/BBB damage in APOE4 carriers.

White Matter Structural Biomarkers Derived from Diffusion Tensor Imaging to Estimate Upper-Extremity Motor Function in Stroke Using Machine Learning - Martín Emiliano Rodríguez-García; Ruben I. Carino-Escobar; Paul Carrillo-Mora; Norma Marín-Arriaga; Ana G. Ramirez-Nava; Claudia Hernandez-Arenas; Ma. del Refugio Pacheco-Gallegos; Jimena Quinzaños-Fresnedo; Jessica Cantillo-Negrete (Brain Topography, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Intentional take of seabirds for human consumption: a global review to inform conservation and policy needs for migratory species - Jonathan M. Handley; Joanne Morten; G. Barry Baker; Aline Küehl-Stenzel; Maximin K. Djondo; Graeme A. Taylor; Iván Ramirez; Heidrun Frisch-Nwakanma; Noëlle F. Kümpel; Tammy E. Davies (Biological Conservation, 2026)

Extreme wave events inferred from large subaerial carbonate boulders on a rocky coast in Pasuquin, Ilocos Norte, Philippines - Edrian M. Tubalado; Noelynna T. Ramos; Lyndon P. Nawanao; Ace Matthew F. Cantillep; Alec Benjamin G. Ramirez; Jelian S. Reyes; Kathrine V. Maxwell; Shou-Yeh Gong; Tsai-Luen Yu; Chuan-Chou Shen (Marine Geology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Accounting for human–nature linkages in area‐based conservation monitoring through social–ecological indicator bundles - Natalie C. Ban; Mark H. Carr; Emily M. Rubidge; Anne Salomon; Joachim Claudet; Arielle Levine; Lindsay Aylesworth; Luisa Ramirez; Jenn M. Burt; Mark Andrachuk; Natascia Tamburello; Rebecca Martone; et al. (Conservation Biology, 2025)
As the coverage of area‐based conservation increases across the globe, it is critical to improve understanding of the social and ecological outcomes of such measures and the pathways to their outcomes. A social–ecological systems approach to monitoring and evaluation is increasingly advocated; yet, applications remain scarce. We sought to facilitate operationalization of this approach through prioritization of indicators when resources are scarce and to improve capture of social–ecological interactions. We convened a working group of practitioners and academics to explore linked social and ecological interactions through a case study of marine protected areas (MPAs). We used causal models (implemented through causal loop diagrams) in participatory and future‐oriented approaches to identify interactions among key nodes of the system that can be a focus of monitoring. These nodes and their interactions provided insight into linked indicators of key system components, for example, biomass, compliance, perceived legitimacy, catches, and perceived fairness. We called these indicator bundles . Indicator bundles can be applied to analyze causal modeling diagrams, identify essential elements to monitor, and inform analytical and reporting protocols. The bundles can also help identify key leverage points for adaptive management to improve outcomes of existing interventions. This approach can inform monitoring and evaluation and, ultimately, the design and adaptive management of conservation areas that maximize social and ecological benefits and minimize negative trade‐offs.

Alternative biological functions of lactose: a narrative review - Augusto Anguita-Ruiz; Hassan Vatanparast; Corinna Walsh; Giovanni Barbara; Sharon Natoli; Bronwyn Eisenhauer; Jaime Ramirez-Mayans; G. Harvey Anderson; Mathilde Guerville; Amandine Ligneul; Angel Gil (Critical Reviews in Food Science and Nutrition, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Lymphocystis Disease Virus Infection in Cultured Three‐Spot Gourami ( Trichogaster trichopterus ) in Brazil - Sóstenes A. C. Marcelino; Leonardo L. Gorza; Sarah P. Carneiro; Ellen C. Oliveira; Luiz F. F. Nogueira; Henrique C. P. Figueiredo; Matheus A. Ramirez; Anibal G. Armien; Guilherme C. Tavares; Felipe Pierezan (Journal of Fish Diseases, 2025)
Lymphocystis disease virus (LCDV) infection induces massive hypertrophy of dermal cells with intracellular accumulation of virions, resulting in skin nodules that are observed to the naked eye. In September 2022, an ornamental fish producer noted white spots and nodules on the skin and fins of a three‐spot gourami ( Trichogaster trichopterus ) population, which compromised the aesthetic of the fish. The disease only affected this fish species in the farm and was intermittent. Ten diseased and four apparently healthy fish were collected during the first sampling, and 20 diseased fish were collected approximately 1 year after for a follow‐up examination. Macroscopically, the fish presented isolated or small clusters of white to grey nodules, measuring 0.1–0.5 mm, concentrated on the fins and caudal peduncle. Histologically, nodules in the skin and internal viscera were composed of numerous hypertrophied cells with nucleolar components and karyomegaly and thick hyaline cell walls. Virions, with a diameter of approximately 180 nm, were visualised in infected interstitial cells in the skin through transmission electron microscopy. The presence of LCDV in the skin, spleen, and kidney was confirmed by specific PCR. Phylogenetic analysis of the MCP gene revealed that the isolates from Brazilian gouramis belonged to the cluster of LCDV genogroup VI, similar to an unclassified virus identified in a population of gouramis in Korea. This report describes the pathological and molecular findings of LCDV infection in cultured three‐spot gourami in Brazil.

Combined hepatocellular carcinoma and cholangiocarcinoma, with sarcomatoid transformation: Histological and immunohistochemical description - E.R. Riera; G. Ramirez; J. Molín; A. Suárez-Bonet (Journal of Comparative Pathology, 2025)

Concomitant intestinal lymphoma and squamous cell Carcinoma in a cat: A case report - E.R. Riera; G. Ramirez; J. Molín (Journal of Comparative Pathology, 2025)

Upcycling textile derived microplastics waste collected from washer and dryers to carbonaceous products using hydrothermal carbonization - Silvia Parrilla-Lahoz; Elena Jiménez-Páez; Mateus G. Masteghin; Joel J. Pawlak; Richard A. Venditti; Robert Bird; Paul Servin; Jose Antonio Odriozola; Tomas Ramirez Reina; Melis S. Duyar (Waste Management, 2025)

Biostimulant Effects of Iodine on the Biomass, Biomolecules, and Nutritional Profile of Lettuce Seedlings - Angie Tatiana Ortega-Ramirez; Oscar Silva-Marrufo; Yazmin E. Perez-Rubio; Oscar G. Alaniz-Villanueva; Jaime Herrera-Gamboa; Rubén I. Marin-Tinoco; Pablo Preciado-Rangel; Oscar Sariñana-Aldaco (Journal of Soil Science and Plant Nutrition, 2025)

Dynamic effect of climate change on flood damage cost in the Andean region of Colombia using an ARDL-ECM model and climate change projections - Camilo A. Rodriguez-Espinosa; Carlos F. Valencia; Carlos G. Ramirez; Carlos D. Valencia (Sustainable Cities and Society, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Assessment of individual and population-based sampling for detection of influenza A virus RNA in breeding swine herds - DCA Moraes; PC Gauger; OH Osemeke; IF Machado; G Cezar; RC Paiva; MP Mil-Homens; MN Almeida; A Ramirez; GS Silva; DCL Linhares (Veterinary Microbiology, 2025)

Groundwater storage loss in the central valley analysis using a novel method based on in situ data compared to GRACE-derived data - Michael D. Stevens; Saul G. Ramirez; Eva-Marie H. Martin; Norman L. Jones; Gustavious P. Williams; Kyra H. Adams; Daniel P. Ames; Sarva T. Pulla (Environmental Modelling & Software, 2025)

Optimized CO2 photoreduction using cuprous oxide (Cu2O) nanoparticles synthesized using Psidium guajava extract - S. Torres-Arellano; E. Luevano-Hipolito; Mayte G. Fabela-Cedillo; J. L. Aleman-Ramirez; Leticia M. Torres-Martínez; P. J. Sebastian (Energy, Ecology and Environment, 2025)
This work aims to propose earth-abundant materials for CO 2 photoreduction to generate renewable solar fuels to provide practical solutions to global warming. The selected material in this case is cuprous oxide (Cu 2 O), one of the most promising photocatalysts for CO 2 photoreduction due to its high affinity to solar radiation and electronic properties. Cu 2 O nanoparticles (NPs) were synthesized using Psidium guajava residue for the photocatalytic CO 2 reduction. The aqueous residue of the Psidium guajava fruit proved to be suitable for stabilizing and acting as a reducing agent for the synthesis of Cu 2 O NPs. The XRD analysis confirmed the formation of the cubic structure of Cu 2 O. The nanoparticles absorb light from 430 nm with a direct bandgap value of around 1.8 eV. Cu 2 O NPs exhibited activity for CO 2 photoreduction, whose efficiency was optimized by an orthogonal Taguchi L 9 design. The factors studied were catalyst loading, air flow, and temperature. During the use of Cu 2 O NPs in the CO 2 photoreduction HCOOH was identified as the main product, with an optimized production of 103.4 µmol h − 1 under visible light. Also, it was demonstrated the photocatalytic activity of the Cu 2 O NPs for H 2 evolution by water splitting. Graphical Abstract

Fumonisins in infant cereals marketed as complementary food in Argentina - Eugenia Cendoya; María J. Nichea; Cindy J. Romero Donato; Vanessa G. L. Zachetti; María del Pilar Monge; María L. Ramirez (Food Additives & Contaminants Part B-Surveillance, 2025)

Recreational hot springs as environmental reservoir of potential multidrug-resistant pathogens - Matteo Selci; Monica Correggia; Angelina Cordone; Marco Guida; Grazia Marina Quero; Roberta Piredda; Costantino Vetriani; Carlos Ramirez; Karen G. Lloyd; J. Maarten de Moor; Peter H. Barry; Matthew O. Schrenk; et al. (Environmental Research, 2024)

An Investigation into the Relationship of Circulating Gut Microbiome Molecules and Inflammatory Markers with the Risk of Incident Dementia in Later Life - Kolade Oluwagbemigun; Andrea Anesi; Urska Vrhovsek; Fulvio Mattivi; Pamela Martino Adami; Michael Pentzek; Martin Scherer; Steffi G. Riedel-Heller; Siegfried Weyerer; Horst Bickel; Birgitt Wiese; Matthias Schmid; et al. (Molecular Neurobiology, 2024)
The gut microbiome may be involved in the occurrence of dementia primarily through the molecular mechanisms of producing bioactive molecules and promoting inflammation. Epidemiological evidence linking gut microbiome molecules and inflammatory markers to dementia risk has been mixed, and the intricate interplay between these groups of biomarkers suggests that their joint investigation in the context of dementia is warranted. We aimed to simultaneously investigate the association of circulating levels of selected gut microbiome molecules and inflammatory markers with dementia risk. This case–cohort epidemiological study included 805 individuals (83 years, 66% women) free of dementia at baseline. Plasma levels of 19 selected gut microbiome molecules comprising lipopolysaccharide, short-chain fatty acids, and indole-containing tryptophan metabolites as well as four inflammatory markers measured at baseline were linked to incident all-cause (ACD) and Alzheimer’s disease dementia (AD) in binary outcomes and time-to-dementia analyses. Independent of several covariates, seven gut microbiome molecules, 5-hydroxyindole-3-acetic acid, indole-3-butyric acid, indole-3-acryloylglycine, indole-3-lactic acid, indole-3-acetic acid methyl ester, isobutyric acid, and 2-methylbutyric acid, but no inflammatory markers discriminated incident dementia cases from non-cases. Furthermore, 5-hydroxyindole-3-acetic acid (hazard ratio: 0.58; 0.36–0.94, P = 0.025) was associated with time-to-ACD. These molecules underpin gut microbiome-host interactions in the development of dementia and they may be crucial in its prevention and intervention strategies. Future larger epidemiological studies are needed to confirm our findings, specifically in exploring the repeatedly measured circulating levels of these molecules and investigating their causal relationship with dementia risk.

Effect of Nicotine on Pulmonary Pathogenic Bacteria - Adrián Rodríguez-Carlos; Oscar E. Gonzalez-Muniz; Maria G. Ramirez-Ledesma; Bruno Rivas-Santiago (Current Microbiology, 2024)

Advanced nonlinear soil-structure interaction model for the seismic analysis of safety-related nuclear structures - J. M. Gonzalez; A. H. Barbat; Y. F. Vargas-Alzate; F. Rastellini; J. Ramirez; C. Escudero; L. G. Pujades (Bulletin of Earthquake Engineering, 2024)
This article proposes an advanced nonlinear soil-structure interaction methodology, for the seismic analysis of a nuclear structure. To do so, a study is performed on a nuclear reinforced concrete structure considering the effects of the nonlinearity due to the sliding and rocking at the soil-structure interface, under a Beyond Design Basis Earthquake . A tridimensional numerical model based on the Finite Element Method is developed for the structure and the soil. The model of the structure considers composite materials to describe all the structural members, taking full advantage of the modelling capabilities of the finite element method. The soil layers are modelled assuming their degraded properties due to the propagation of the seismic ground motion. An innovative approach to achieve spectral matching at the surface of the FEM soil model after propagation from the bedrock has been successfully implemented. The seismic analysis on the structure has been performed by considering three hypotheses for the contact between soil and structure: fixed-base, fixed contact and sliding-rocking contact. Insights are provided after comparing floor spectra for the contact approaches assessed in this research, calculated at the systems and components’ locations at the nuclear structure. Finally, a statistical approach for the soil properties allows to study the effects of these uncertainties on the structural response.

Mineralogy and geochemistry of siliciclastic rocks from the Cintura Formation in the Cabullona area, Sonora, Mexico - Saira A. Pacheco Olivas; Jayagopal Madhavaraju; Inocente G. Espinoza-Maldonado; Erik Ramirez-Montoya; Rogelio Monreal; Martin Valencia Moreno; Francisco J. Grijalva-Noriega; Teresa Pi Puig (Journal of Sedimentary Environments, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Shake-table testing of a stone masonry building aggregate: overview of blind prediction study - I. Tomić; A. Penna; M. DeJong; C. Butenweg; A. A. Correia; P. X. Candeias; I. Senaldi; G. Guerrini; D. Malomo; B. Wilding; D. Pettinga; M. Spanenburg; et al. (Bulletin of Earthquake Engineering, 2024)
City centres of Europe are often composed of unreinforced masonry structural aggregates, whose seismic response is challenging to predict. To advance the state of the art on the seismic response of these aggregates, the Adjacent Interacting Masonry Structures (AIMS) subproject from Horizon 2020 project Seismology and Earthquake Engineering Research Infrastructure Alliance for Europe (SERA) provides shake-table test data of a two-unit, double-leaf stone masonry aggregate subjected to two horizontal components of dynamic excitation. A blind prediction was organized with participants from academia and industry to test modelling approaches and assumptions and to learn about the extent of uncertainty in modelling for such masonry aggregates. The participants were provided with the full set of material and geometrical data, construction details and original seismic input and asked to predict prior to the test the expected seismic response in terms of damage mechanisms, base-shear forces, and roof displacements. The modelling approaches used differ significantly in the level of detail and the modelling assumptions. This paper provides an overview of the adopted modelling approaches and their subsequent predictions. It further discusses the range of assumptions made when modelling masonry walls, floors and connections, and aims at discovering how the common solutions regarding modelling masonry in general, and masonry aggregates in particular, affect the results. The results are evaluated both in terms of damage mechanisms, base shear forces, displacements and interface openings in both directions, and then compared with the experimental results. The modelling approaches featuring Discrete Element Method (DEM) led to the best predictions in terms of displacements, while a submission using rigid block limit analysis led to the best prediction in terms of damage mechanisms. Large coefficients of variation of predicted displacements and general underestimation of displacements in comparison with experimental results, except for DEM models, highlight the need for further consensus building on suitable modelling assumptions for such masonry aggregates.

Sediment analysis and water quality assessment in the Pixquiac basin: drinking water supply of Xalapa city (Veracruz, Mexico) - M. C. Dupont; E. Martinez-Tavera; P. F. Rodriguez-Espinosa; A. G. Hernandez-Ramirez; P. Guadarrama Guzmán (Environmental Monitoring and Assessment, 2024)

Comparison of thermo-hydraulic performance among different 3D printed periodic open cellular structures - S. Richard; D. Tasso; M. Rajana; A Saker; A. Ramirez Santos; C. Makhloufi; N. Meynet; B. Hary; S. Nardone; G. Marino; M. Thomas; C. Italiano; et al. (Chemical Engineering Journal, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

A geophysical assessment of the Termas de Río Valdez geothermal area (Tierra del Fuego, Argentina) - Jorge G. Lozano; Donaldo M. Bran; Sebastian Ramirez; Florencia B. Restelli; Stefania Bunicontro; Federico Esteban; Marco Menichetti; Emanuele Lodolo; Alberto Renzulli; Juan F. Vilas; Alejandro Tassone (Geothermics, 2024)

Safe plates in the school space: Investigating compliance of food safety standards among school-based food service providers - Realyn Q. Salvador; Charizza Mae T. Borromeo; Gary C. Alnas; Shaira Vita Mae G. Adviento; Alma C. Asuncion; Mark R. Limon; Arnelyn B. Esteban; Aprilyn A. Gajete; Shiela Mae L. Garcia; Jherie-Mae R. Parico; Christian Jay P. Pungtilan; Jaypee Carl D. Respicio; et al. (Food and Humanity, 2024)

Comparing environmental impacts of deep‐seabed and land‐based mining: A defensible framework - A. Metaxas; C. D. Anglin; A. Cross; J. Drazen; M. Haeckel; G. Mudd; C. R. Smith; S. Smith; P. P. E. Weaver; L. Sonter; D. J. Amon; P. D. Erskine; et al. (Global Change Biology, 2024)
The crises of climate change and biodiversity loss are interlinked and must be addressed jointly. A proposed solution for reducing reliance on fossil fuels, and thus mitigating climate change, is the transition from conventional combustion‐engine to electric vehicles. This transition currently requires additional mineral resources, such as nickel and cobalt used in car batteries, presently obtained from land‐based mines. Most options to meet this demand are associated with some biodiversity loss. One proposal is to mine the deep seabed, a vast, relatively pristine and mostly unexplored region of our planet. Few comparisons of environmental impacts of solely expanding land‐based mining versus extending mining to the deep seabed for the additional resources exist and for biodiversity only qualitative. Here, we present a framework that facilitates a holistic comparison of relative ecosystem impacts by mining, using empirical data from relevant environmental metrics. This framework (Environmental Impact Wheel) includes a suite of physicochemical and biological components, rather than a few selected metrics, surrogates, or proxies. It is modified from the “recovery wheel” presented in the International Standards for the Practice of Ecological Restoration to address impacts rather than recovery. The wheel includes six attributes (physical condition, community composition, structural diversity, ecosystem function, external exchanges and absence of threats). Each has 3–5 sub attributes, in turn measured with several indicators. The framework includes five steps: (1) identifying geographic scope; (2) identifying relevant spatiotemporal scales; (3) selecting relevant indicators for each sub‐attribute; (4) aggregating changes in indicators to scores; and (5) generating Environmental Impact Wheels for targeted comparisons. To move forward comparisons of land‐based with deep seabed mining, thresholds of the indicators that reflect the range in severity of environmental impacts are needed. Indicators should be based on clearly articulated environmental goals, with objectives and targets that are specific, measurable, achievable, relevant, and time bound.

Characterization of free-field seismic motions for soil-structure interaction analysis of nuclear structures using enhanced transfer functions - Yeudy F. Vargas-Alzate; Alex H. Barbat; Lluis G. Pujades; Luis A. Pinzón; Jose M. Gonzalez; Junior Ramirez; Fernando Rastellini (Soil Dynamics and Earthquake Engineering, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Optimization of the Polarized Imaging Nephelometer (PI-Neph) for continuous monitoring of multiwavelength aerosol phase functions in support of space polarimetry missions - E. Bazo; J.V. Martins; D. Perez-Ramirez; A. Valenzuela; G. Titos; A. Cazorla; D. Fuertes; M. Weiss; A. Turpie; C. Li; F.J. García-Izquierdo; I. Foyo-Moreno; et al. (Atmospheric Environment, 2024)

P22-21: A 3D human iPSC-derived brain model coupled to multi-well high-density microelectrode arrays (HD-MEA) to improve in vitro neurotoxicity screening of environmental compounds - D. Pamies; K. Carstens; E. Gronskaya; D. Jaeckel; J. Bertoli; K. Ramirez; T. Shafer; M.-G. Zurich (Toxicology Letters, 2023)

Circulating Plasma miRNA Homologs in Mice and Humans Reflect Familial Cerebral Cavernous Malformation Disease - Sharbel G. Romanos; Abhinav Srinath; Ying Li; Bingqing Xie; Chang Chen; Yan Li; Thomas Moore; Dehua Bi; Je Yeong Sone; Rhonda Lightle; Nick Hobson; Dongdong Zhang; et al. (Translational Stroke Research, 2023)

Fertility of conventional and of sex-sorted stallion sperm using SexedULTRA™ Genesis III technology - Juan C Samper; Camilo Hernandez; Luisa Ramirez-Agames; Sheila G Spachek; Pablo Ross; Cristina Cabrera; Charles C Love (Journal of Equine Veterinary Science, 2023)

Recent trends in management strategies for two major maize borers: Ostrinia nubilalis and Sesamia nonagrioides - Gülay Kaçar; Ana Butrón; Dimitrios Kontogiannatos; Peng Han; Maria Fernanda G. V. Peñaflor; Gema P. Farinós; Fangneng Huang; William D. Hutchison; Bruno H. S. de Souza; Rosa Ana Malvar; Anna Kourti; Ricardo Ramirez-Romero; et al. (Journal of Pest Science, 2023)

Exploring practical nutrition options for maximizing seed yield and protein concentration in soybean - Guido Di Mauro; Raí Schwalbert; Santiago Alvarez Prado; Matías G. Saks; Hugo Ramirez; Jerónimo Costanzi; Gonzalo Parra (European Journal of Agronomy, 2023)

Real-time COVID-19 Education to Reduce Workplace Risks: Thematic Analysis of a COVID-19 Agricultural Employer Webinar Series - Caitlin G. Jones; Yajaira Ramirez Sigala; Teresa Andrews; Heather E. Riden (Journal of Agromedicine, 2023)

Prospects and challenges of environmental DNA (eDNA) metabarcoding in mangrove restoration in Southeast Asia - Alison K. S. Wee; Severino G. Salmo III; Kannan Sivakumar; Amy Y-H Then; Mohammad Basyuni; Jean Fall; Kazi Ahsan Habib; Yukinobu Isowa; Venus Leopardas; Nasreen Peer; Maria D. Artigas-Ramirez; Kithsiri Ranawana; et al. (Frontiers in Marine Science, 2023)
Species detection using environmental DNA (eDNA) is a biomonitoring tool that can be widely applied to mangrove restoration and management. Compared to traditional surveys that are taxa-specific and time-consuming, eDNA metabarcoding offers a rapid, non-invasive and cost-efficient method for monitoring mangrove biodiversity and characterising the spatio-temporal distribution of multiple taxa simultaneously. General guidelines for eDNA metabarcoding are well-established for aquatic systems, but habitat-specific guidelines are still lacking. Mangrove habitats, as priority ecosystems for restoration in Southeast Asia, present unique prospects and challenges in these regards. Environmental DNA metabarcoding can be used to (1) track functional recovery in ecological restoration, (2) prioritise conservation areas, (3) provide early warning for threats, (4) monitor threatened taxa, (5) monitor response to climate change, and (6) support community-based restoration. However, these potential applications have yet been realized in Southeast Asia due to (1) technical challenges, (2) lack of standardised methods, (3) spatio-temporal difficulties in defining community, (4) data limitations, and (5) lack of funding, infrastructure and technical capacity. Successful implementation of eDNA metabarcoding in mangrove restoration activities would encourage the development of data-driven coastal management and equitable conservation programs. Eventually, this would promote Southeast Asia’s shared regional interests in food security, coastal defence and biodiversity conservation.

Effects of lignocellulosic biomass type on the economics of hydrothermal treatment of digested sludge for solid fuel and soil amendment applications - Majid Ebrahimi; Jerome A. Ramirez; John G. Outram; Kameron Dunn; Paul D. Jensen; Ian M. O'Hara; Zhanying Zhang (Waste Management, 2023)

Economic analysis of the benefits to petroleum refiners for low carbon boosted spark ignition biofuels - Nicholas A. Carlson; Avantika Singh; Michael S. Talmadge; Yuan Jiang; George G. Zaimes; Shuyun Li; Troy R. Hawkins; Lauren Sittler; Aaron Brooker; Daniel J. Gaspar; Robert L. McCormick; M.M. Ramirez-Corredores (Fuel, 2023)

Economic and environmental analysis to evaluate the potential value of co-optima diesel bioblendstocks to petroleum refiners - Yuan Jiang; George G. Zaimes; Shuyun Li; Troy R. Hawkins; Avantika Singh; Nicholas Carlson; Michael Talmadge; Daniel J. Gaspar; M.M. Ramirez-Corredores; Andrew W. Beck; Ben Young; Lauren Sittler; et al. (Fuel, 2023)

The response of soil physical quality parameters to a perennial grain crop - E.J. Daly; K. Kim; G. Hernandez-Ramirez; K. Klimchuk (Agriculture, Ecosystems & Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Eustress application trough-controlled elicitation strategies as an effective agrobiotechnology tool for capsaicinoids increase: a review - Laura Helena Caicedo-Lopez; Ramon G. Guevara-Gonzalez; Aurea K. Ramirez-Jimenez; Ana A. Feregrino-Perez; Luis Miguel Contreras-Medina (Phytochemistry Reviews, 2022)

Impacts of Mineralogy on Petrophysical Properties - Maira C. O. Lima; Elizabeth M. Pontedeiro; Mateus G. Ramirez; Julia Favoreto; Hélisson N. dos Santos; Martinus Th. van Genuchten; Leonardo Borghi; Paulo Couto; Amir Raoof (Transport in Porous Media, 2022)
Because of their extreme heterogeneity at multiple scales, carbonate rocks present a great challenge for studying and managing oil reservoirs. Depositional processes and diagenetic alterations of carbonates may have produced very complex pore structures and, consequently, variable fluid storage and flow properties of hydrocarbon reservoirs. To understand the impact of mineralogy on the pore system, we analyzed four carbonate rock samples (coquinas) from the Morro do Chaves Formation in Brazil. For this study, we used thin sections and XRD for their mineralogical characterization, together with routine core analysis, NMR, MICP and microCT for the petrophysical characterizations. The samples revealed very similar porosity values but considerably different permeabilities. Samples with a relatively high quartz content (terrigenous material) generally had lower permeabilities, mostly caused by more mineral fragmentation. Samples with little or no quartz in turn exhibited high permeabilities due to less fragmentation and more diagenetic actions (e.g., dissolution of shells). Results confirm that carbonate minerals are very susceptible to diagenesis, leading to modifications in their pore body and pore throat sizes, and creating pores classified as moldic and vug pores, or even clogging them. For one of the samples, we acquired detailed pore skeleton information based on microCT images to obtain a more complete understanding of its structural characteristics.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Anti-oxidant and anti-inflammatory effect of polar extracts obtained from waste product of wine making - M. J. Germanó; M. D. Muñoz; M. C. Della-Vedova; G. E. Feresin; M. Rinaldi-Tosi; R. D. Enriz; D. C. Ramirez; F. A. Giannini (Natural Product Research, 2021)

The PMEL gene and merle (dapple) in the dachshund: cryptic, hidden, and mosaic variants demonstrate the need for genetic testing prior to breeding - Blake C. Ballif; Lisa J. Emerson; Christina J. Ramirez; Casey R. Carl; Kyle Sundin; Helen Flores-Smith; Lisa G. Shaffer (Human Genetics, 2021)

Biological Synthesis of PbS, As3S4, HgS, CdS Nanoparticles using Pseudomonas aeruginosa and their Structural, Morphological, Photoluminescence as well as Whole Cell Protein Profiling Studies - Annika Durve Gupta; Arvind Gupta; Almendra Reyes-Calderón; Victor Ishrayelu Merupo; Golap Kalita; Jośe Herrera-Celis; Naresh Chandra; Ashutosh Sharma; Jose Tapia Ramirez; L. G. Arriaga; Goldie Oza (Journal of Fluorescence, 2021)

Novel atypical Aeromonas salmonicida bath challenge model for juvenile ballan wrasse ( Labrus bergylta, Ascanius) - Athina Papadopoulou; Kathryn Garvey; Tom Hill; Jose G. Ramirez‐Paredes; Sean J. Monaghan; Johanna L. Baily; Andrew Davie; Ioanna Katsiadaki; David Verner‐Jeffreys; Timothy Wallis; Herve Migaud; Alexandra Adams (Journal of Fish Diseases, 2021)
Atypical Aeromonas salmonicida (a As ) is currently one of the most routinely recovered bacterial pathogens isolated during disease outbreaks in farmed cleaner fish, ballan wrasse ( Labrus bergylta , Ascanius). Vibrionaceae family bacteria have also been isolated from ballan wrasse in Scotland. This study determined the infectivity, pathogenicity and virulence of a As and Vibrionaceae isolates in juvenile farmed ballan wrasse ( n = 50; approx. 2 g) using a bath challenge, and fish were monitored for a period of 16 days. Atypical As caused significant mortalities in contrast to Vibrionaceae isolates. Notably, differential virulence was observed between two a As vapA type V strains at similar challenge doses. Diseased fish exhibited a systemic infection where a As was detected in all analysed tissues (liver, spleen and kidney) by PCR and qPCR. Macroscopically, moribund and survivor fish exhibited hepatomegaly and splenomegaly. In moribund and surviving fish, histopathology showed granulomatous hepatitis with eosinophilic granular cells surrounding bacterial colonies and endocarditis along with splenic histiocytosis. This is the first report of a successful a As bath challenge model for juvenile ballan wrasse which provides an important tool for future studies on vaccine efficacy and immunocompetence.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Immature ticks on wild birds and the molecular detection of a novel Rickettsia strain in the Ibitipoca State Park, southeastern Brazil - Diego G. Ramirez; Hermes R. Luz; Sebastián Muñoz-Leal; Walter Flausino; Igor C. L. Acosta; Thiago F. Martins; Maristela Peckle; Helio F. Santos; Guilherme P. Furusawa; Marcelo B. Labruna; João L. H. Faccini (Experimental and Applied Acarology, 2020)

Numerical simulation of 1-D oil and water displacements in petroleum reservoirs using the correction procedure via reconstruction (CPR) method - G. Galindez-Ramirez; D. K. E. Carvalho; P. R. M. Lyra (Computational Geosciences, 2020)

Sea Turtles at Serrana Island and Serranilla Island, Seaflower Biosphere Reserve, Colombian Caribbean - Cristian Ramirez-Gallego; Karla G. Barrientos-Muñoz (Frontiers in Marine Science, 2020)

Climate change favors rice production at higher elevations in Colombia - F. Castro-Llanos; G. Hyman; J. Rubiano; J. Ramirez-Villegas; H. Achicanoy (Mitigation and Adaptation Strategies for Global Change, 2019)

Éxito!: Making an Impact in Training Latinos for Doctorates and Cancer Research - Amelie G. Ramirez; Kipling J. Gallion; Arely Perez; Rebecca T. Adeigbe; Edgar Munoz; Rena J. Pasick (Journal of Cancer Education, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Quality assurance checklist and additional considerations for canine clinical genetic testing laboratories: a follow-up to the published standards and guidelines - Lisa G. Shaffer; Anja Geretschlaeger; Christina J. Ramirez; Blake C. Ballif; Casey Carl (Human Genetics, 2019)

Standards and guidelines for canine clinical genetic testing laboratories - Lisa G. Shaffer; Kyle Sundin; Anja Geretschlaeger; Julia Segert; June E. Swinburne; Ramon Royal; Robert Loechel; Christina J. Ramirez; Blake C. Ballif (Human Genetics, 2019)

Plasmonic gold chips for the diagnosis of Toxoplasma gondii, CMV, and rubella infections using saliva with serum detection precision - Xiaoyang Li; Christelle Pomares; François Peyron; Cynthia J. Press; Raymund Ramirez; Gonfrier Geraldine; Isabelle Cannavo; Emmanuelle Chapey; Pauline Levigne; Martine Wallon; Jose G. Montoya; Hongjie Dai (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

Inflammatory and Anti-inflammatory Responses Co-exist Inside Lung Granuloma of Fatal Cases of Coccidioidomycosis: A Pilot Report - Heidi G. Rodriguez-Ramirez; Adolfo Soto-Dominguez; Gloria M. González; Oralia Barboza-Quintana; Mario C. Salinas-Carmona; Luis A. Ceceñas-Falcon; Roberto Montes-de-Oca-Luna; Alma Y. Arce-Mendoza; Adrian G. Rosas-Taraco (Mycopathologia, 2018)

Discovery of Transcription Factors Novel to Mouse Cerebellar Granule Cell Development Through Laser-Capture Microdissection - Peter G. Y. Zhang; Joanna Yeung; Ishita Gupta; Miguel Ramirez; Thomas Ha; Douglas J. Swanson; Sayaka Nagao-Sato; Masayoshi Itoh; Hideya Kawaji; Timo Lassmann; Carsten O. Daub; Erik Arner; et al. (The Cerebellum, 2018)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

How will the ‘cancer moonshot’ impact health disparities? - Amelie G. Ramirez; Ian M. Thompson (Cancer Causes & Control, 2017)

Ambulatory blood pressure response to a bout of HIIT in metabolic syndrome patients - M. Ramirez-Jimenez; F. Morales-Palomo; J. G. Pallares; Ricardo Mora-Rodriguez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Comparative study of As, Cd, Cu, Cr, Mg, Mn, Ni, Pb and Zn concentrations between sediment and water from estuary and port - I. Bejarano-Ramirez; Jose M. Jurado; R. Muñiz-Valencia; Á. Alcázar; Silvia G. Ceballos-Magaña; A. Olivos-Ortiz; O. Rangel (International Journal of Environmental Science and Technology, 2017)

The National Cancer Institute R25 Cancer Education Grants Program: A Workshop Report - Jeannette F. Korczak; Davyd W. Chung; Erica Rosemond; Daniel D. Von Hoff; Richard L. Haspel; John W. Waterbor; Shine Chang; Amelie G. Ramirez; Susan Perkins; Jonathan Wiest; Ming Lei (Journal of Cancer Education, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Identification and characterization of large DNA deletions affecting oil quality traits in soybean seeds through transcriptome sequencing analysis - Wolfgang Goettel; Martha Ramirez; Robert G. Upchurch; Yong-qiang Charles An (Theoretical and Applied Genetics, 2016)

Environmental PCBs in Guánica Bay, Puerto Rico: implications for community health - Naresh Kumar; Daisy Ramirez-Ortiz; Helena M. Solo-Gabriele; Joseph B. Treaster; Olveen Carrasquillo; Michal Toborek; Sapna Deo; Jim Klaus; Leonidas G. Bachas; David Whitall; Sylvia Daunert; Jose Szapocznik (Environmental Science and Pollution Research, 2016)

Promotora Outreach, Education and Navigation Support for HPV Vaccination to Hispanic Women with Unvaccinated Daughters - Deborah Parra-Medina; Daisy Y. Morales-Campos; Cynthia Mojica; Amelie G. Ramirez (Journal of Cancer Education, 2015)

Anuran trypanosomes: phylogenetic evidence for new clades in Brazil - Juliana I. G. da S. Ferreira; Andrea P. da Costa; Diego Ramirez; Jairo A. M. Roldan; Danilo Saraiva; Gislene F. R. da S. Founier; Ana Sue; Erick R. Zambelli; Antonio H. H. Minervino; Vanessa K. Verdade; Solange M. Gennari; Arlei Marcili (Systematic Parasitology, 2015)

Spiderling sex ratio and maternal investment in the bolas spider Mastophora cornigera (Araneae, Araneidae) - Martina G. Ramirez; Celina M. Oliveri; Dina Mismar; Amy Barsoum; Jasmin Abdulla (Invertebrate Reproduction & Development, 2015)

Climate‐driven spatial mismatches between British orchards and their pollinators: increased risks of pollination deficits - Chiara Polce; Michael P Garratt; Mette Termansen; Julian Ramirez‐Villegas; Andrew J Challinor; Martin G Lappage; Nigel D Boatman; Andrew Crowe; Ayenew Melese Endalew; Simon G Potts; Kate E Somerwill; Jacobus C Biesmeijer (Global Change Biology, 2014)
Understanding how climate change can affect crop‐pollinator systems helps predict potential geographical mismatches between a crop and its pollinators, and therefore identify areas vulnerable to loss of pollination services. We examined the distribution of orchard species (apples, pears, plums and other top fruits) and their pollinators in Great Britain, for present and future climatic conditions projected for 2050 under the SRES A1B Emissions Scenario. We used a relative index of pollinator availability as a proxy for pollination service. At present, there is a large spatial overlap between orchards and their pollinators, but predictions for 2050 revealed that the most suitable areas for orchards corresponded to low pollinator availability. However, we found that pollinator availability may persist in areas currently used for fruit production, which are predicted to provide suboptimal environmental suitability for orchard species in the future. Our results may be used to identify mitigation options to safeguard orchard production against the risk of pollination failure in Great Britain over the next 50 years; for instance, choosing fruit tree varieties that are adapted to future climatic conditions, or boosting wild pollinators through improving landscape resources. Our approach can be readily applied to other regions and crop systems, and expanded to include different climatic scenarios.

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Technique for Restoration of Mite (Acari) Preparations in Deteriorated Hoyer’s Medium - F C Jacinavicius; J C Badari; D G Ramirez; R H P Moraes; V C Onofrio; D M Barros-Battesti (Neotropical Entomology, 2013)

Description of larva of Amblyomma romitii (Acari: Ixodidae) by optical and scanning electron microscopy, including porotaxy and phylogenetic analysis - Darci M. Barros-Battesti; Diego G. Ramirez; Janio dos Santos Sampaio; Katia M. Famadas; João Luiz H. Faccini; Pablo Henrique Nunes; Thiago F. Martins; Maria Ogrzewalska; Marcelo B. Labruna; Arlei Marcili; Fabio da Silva Barbieri (Experimental and Applied Acarology, 2013)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Population structure and reproductive patterns of the NW Mediterranean deep-sea macrourid Trachyrincus scabrus (Rafinesque, 1810) - U. Fernandez-Arcaya; L. Recasens; H. Murua; E. Ramirez-Llodra; G. Rotllant; J. B. Company (Marine Biology, 2012)

Natural occurrence of alternariol and alternariol monomethyl ether in soya beans - M. S. Oviedo; G. G. Barros; S. N. Chulze; M. L. Ramirez (Mycotoxin Research, 2012)

Vertical density gradient in the eastern North Atlantic during the last 30,000 years - M. Rogerson; G. R. Bigg; E. J. Rohling; J. Ramirez (Climate Dynamics, 2012)

Natural deoxynivalenol occurrence and genotype and chemotype determination of a field population of the Fusarium graminearum complex associated with soybean in Argentina - G. Barros; M.S. Alaniz Zanon; A. Abod; M.S. Oviedo; M.L. Ramirez; M.M. Reynoso; A. Torres; S. Chulze (Food Additives & Contaminants: Part A, 2012)

Effects of temperature during soybean seed development on defense-related gene expression and fungal pathogen accumulation - Robert G. Upchurch; Martha E. Ramirez (Biotechnology Letters, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Widespread expression of inducible NOS and citrulline in lupus nephritis tissues - J. J. Bollain-y-Goytia; R. Ramírez-Sandoval; L. Daza; E. Esparza; O. Barbosa; D. Ramirez; G. Pacheco-Tovar; E. Avalos-Diaz; C. Rodríguez-Padilla; R. Herrera-Esparza (Inflammation Research, 2009)

Migratory movements and surfacing rates of humpback whales ( Megaptera novaeangliae ) satellite tagged at Socorro Island, Mexico - Barbara A. Lagerquist; Bruce R. Mate; Joel G. Ortega‐Ortiz; Martha Winsor; Jorge Urbán‐Ramirez (Marine Mammal Science, 2008)
Humpback whales wintering in the Revillagigedo Archipelago, Mexico, have been considered a different subpopulation from those found off mainland Mexico and Baja California. The primary feeding grounds for Revillagigedo humpbacks remain unknown. In February 2003, we deployed 11 Argos satellite‐monitored radio tags to track movements and surfacings of humpback whales (five adults without calves, five mothers with calves, one calf) off Socorro Island in the Revillagigedo Archipelago. Tracking ranged from 222 to 10,481 km over 4.9–149.1 d. Eight whales left Socorro Island: five visited other Mexican wintering destinations, seven moved north of these areas. Migration routes were primarily offshore (average 444 km). Two whales were tracked to feeding grounds: one to British Columbia (46 d migration), and one to Alaska (49 d migration). Mean travel speeds were 1.2 km/h in wintering areas, 4.0 km/h during migration, and 2.2 km/h in feeding areas. Overall surfacing rates ranged from 21 to 88 surfacings/h. Surfacing rates differed between the calf and all other whales, and between feeding areas and migratory/wintering areas for the calf and an adult without a calf. The calf also showed diel variation in surfacing rates. The offshore habits of tagged whales may explain scarce resightings of Revillagigedo humpbacks outside the Revillagigedo Archipelago.

In vitro propagation of ten threatened species of Mammillaria (Cactaceae) - R. Ramirez-Malagon; I. Aguilar-Ramirez; A. Borodanenko; L. Perez-Moreno; J. L. Barrera-Guerra; H. G. Nuñez-Palenius; N. Ochoa-Alejo (In Vitro Cellular & Developmental Biology - Plant, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.

Diversity of human rotaviruses detected in Sicily, Italy, over a 5-year period (2001–2005) - S. De Grazia; S. Ramirez; G. M. Giammanco; C. Colomba; V. Martella; C. Lo Biundo; R. Mazzola; S. Arista (Archives of Virology, 2007)

Mapping QTLs controlling flowering date in Miscanthus sinensis Anderss. - S. G. Atienza; M. C. Ramirez; A. Martin (Cereal Research Communications, 2003)

Glaciers and Climate in the Andes between the Equator and 30° S: What is Recorded under Extreme Environmental Conditions? - U. Schotterer; M. Grosjean; W. Stichler; P. Ginot; C. Kull; H. Bonnaveira; B. Francou; H. W. Gäggeler; R. Gallaire; G. Hoffmann; B. Pouyaud; E. Ramirez; et al. (Climatic Change, 2003)

Deep molecular divergence in the absence of morphological and ecological change in the Californian coastal dune endemic trapdoor spider Aptostichus simus - J. E. Bond; M. C. Hedin; M. G. Ramirez; B. D. Opell (Molecular Ecology, 2001)
Aptostichus simus is a trapdoor spider endemic to the coastal dunes of central and southern California and, on morphological grounds, is recognized as a single species. Mitochondrial DNA 16S rRNA sequences demonstrate that most populations are fixed for the same haplotype and that the population haplotypes from San Diego County, Los Angeles County, Santa Rosa Island, and Monterey County are extremely divergent (6–12%), with estimated separation times ranging from 2 to 6 million years. A statistical cluster analysis of morphological features demonstrates that this genetic divergence is not reflected in anatomical features that might signify ecological differentiation among these lineages. The species status of these divergent populations of A. simus depends upon the species concept utilized. If a time‐limited genealogical perspective is employed, A. simus would be separated at the base into two genetically distinct species. This study suggests that species concepts based on morphological distinctiveness, in spider groups with limited dispersal capabilities, probably underestimate true evolutionary diversity.

Control of Cell pH in the T84 Colon Cell Line - M.A. Ramirez; R. Toriano; M. Parisi; G. Malnic (The Journal of Membrane Biology, 2000)

Permeation of NH3/NH4 + and cell pH in colonic crypts of the rat - M. Ramirez; R. Fernandez; G. Malnic (Pflügers Archiv - European Journal of Physiology, 1999)

Permeation of NH 3 /NH 4 + and cell pH in colonic crypts of the rat - M. Ramirez; R. Fernandez; G. Malnic (Pflügers Archiv - European Journal of Physiology, 1999)

Repopulation and culture of the Pacific Calico scallops in Bahia Concepcion, Baja California Sur, Mexico - E.F. Felix-Pico; A. Tripp-Quezada; J.L. Castro-Ortiz; G. Serrano-Casillas; P.G. Gonzalez-Ramirez; M. Villalejo-Fuerte; R. Palomares-Garcia; F.A. Garcia-Dominguez; M. Mazon-Suastegui; G. Bojorquez-Verastica; G. Lopez-Garcia (Aquaculture International, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Minimal Genetic Variation in a Coastal Dune Arthropod: The Trapdoor Spider Aptostichus simus ( Cyrtaucheniidae ) - Martin G. Ramirez; Julie L. Froehlig (Conservation Biology, 1997)

Rapid test for determination of urea hydrolysis - S. M. Hussain Qadri; Sabiha Zubairi; H. P. Hawley; H. H. Mazlaghani; E. G. Ramirez (Antonie van Leeuwenhoek, 1984)